Histopathological Findings in Dilatation and Curettage in Perimenopausal Age Group Women with Abnormal Uterine Bleeding in Tertiary Care Centre - Kayastha, Bhagirathi; Shrestha, Buddhi Kumar; Pradhan, Alok (Journal of College of Medical Sciences-Nepal, 2025)
Background Abnormal uterine bleeding (AUB) is the commonest presenting complaint in the perimenopausal age group. Histopathological examination (HPE) of endometrial tissue obtained by dilatation and curettage (D and C) is the preferred modality of investigation to determine the endometrial pathology. This study aimed to find out the clinical and histopathological findings in perimenopausal women presenting with AUB. Methods This cross sectional study was conducted in Department of Obstetrics and Gynecology, College of Medical Sciences Teaching Hospital (COMS-TH), Bharatpur, Chitwan, Nepal from November 2024 to April 2025. Ethical approval was obtained from the Institutional Review Committee (IRC) of COMS-TH. Non probability convenient sampling technique was used for data collection. This study was conducted among 125 women selected for D and C. Endometrial tissue was collected and sent for HPE. Data was entered in Microsoft Excel 2016 and analyzed using Statistical Package for Social Science (SPSS), version 16. Results The commonest age group was 40-45 years (46.4%) with mean ±SD of age 46.84 ± 4.83 years. Regarding gravida, 81.6% women were multipara, 7.2% primipara and 6.4% grand multipara. The commonest clinical presentation was menorrhagia (39.2%) followed by metrorrhagia (28.8%). Secretory endometrium (28%) was the commonest histopathological finding followed by disordered proliferative endometrium (27.2%), proliferative endometrium (16%), endometritis (11.2), endometrial polyp (7.2%), endometrial hyperplasia (2.4%) and endometrial carcinoma (1.6%). Conclusions Menorrhagia followed by metrorrhagia is the most common presentation of perimenopausal abnormal uterine bleeding. D and C reveals varied endometrial changes, most commonly normal cyclical and disordered proliferative patterns. Endometrial hyperplasia and carcinoma are less frequent. D & C remains a valuable diagnostic and conservative management tool.